Profiling non-coding RNA levels with clinical classifiers in pediatric Crohn’s disease - Pelia, Ranjit (BMC Med Genomics, 2021)
BACKGROUND: Crohn’s disease (CD) is a heritable chronic inflammatory disorder. Non-coding RNAs (ncRNAs) play an important role in epigenetic regulation by affecting gene expression, but can also directly affect protein function, thus having a substantial impact on biological processes. We investigated whether non-coding RNAs (ncRNA) at diagnosis are dysregulated during CD at different CD locations and future disease behaviors to determine if ncRNA signatures can serve as an index to outcomes. METHODS: Using subjects belonging to the RISK cohort, we analyzed ncRNA from the ileal biopsies of 345 CD and 71 non-IBD controls, and ncRNA from rectal biopsies of 329 CD and 61 non-IBD controls. Sequence alignment was done (STAR package) using Human Genome version 38 (hg38) as reference panel. The differential expression (DE) analysis was performed with EdgeR package and DE ncRNAs were identified with a threshold of fold change (FC) > 2 and FDR < 0.05 after multiple test corrections. RESULTS: In total, we identified 130 CD specific DE ncRNAs (89 in ileum and 41 in rectum) when compared to non-IBD controls. Similarly, 35 DE ncRNAs were identified between B1 and B2 in ileum, whereas no differences among CD disease behaviors were noticed in rectum. We also found inflammation specific ncRNAs between inflamed and non-inflamed groups in ileal biopsies. Overall, we observed that expression of mir1244-2, mir1244-3, mir1244-4, and RN7SL2 were increased during CD, regardless of disease behavior, location, or inflammatory status. Lastly, we tested ncRNA expression at baseline as potential tool to predict the disease status, disease behaviors and disease inflammation at 3-year follow up. CONCLUSIONS: We have identified ncRNAs that are specific to disease location, disease behavior, and disease inflammation in CD. Both ileal and rectal specific ncRNA are changing over the course of CD, specifically during the disease progression in the intestinal mucosa. Collectively, our findings show changes in ncRNA during CD and may have a clinical utility in early identification and characterization of disease progression. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12920-021-01041-7.